Idiopathic scoliosis in subjects with eye diseases: A systematic review with meta‐analysis - Gallego‐Siles, Juan Ramón; Siles‐Fuentes, María José; Ibáñez‐Vera, Alfonso Javier; Cortés‐Pérez, Irene; Obrero‐Gaitán, Esteban; Lomas‐Vega, Rafael (Annals of the New York Academy of Sciences, 2024)
Our aim was to find the best evidence on the prevalence of idiopathic scoliosis (IS) in subjects with eye diseases (EDs) and to determine the most common visual alterations that are present. Following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA), a bibliographic search up to June 2023 in the PubMed, PsycINFO, SCOPUS, and CINAHL Complete databases was performed. Observational studies were selected and the results were analyzed with prevalence odds ratio (OR). A total of six studies, including 18,396 subjects, were selected. The group of subjects with EDs was made up of 6048 individuals, of whom 655 (10.83%) had IS. The group of subjects without EDs was made up of 12,348 individuals of whom 444 (3.60%) presented with IS with an OR = 2.91, CI (95%) = [1.75, 4.83]. Blindness was assessed in a single study with an OR = 7.83, CI (95%) = [1.66, 36.90]; all three studies in the refractive error subgroup yielded an OR = 2.24, CI (95%) = [1.10, 4.58]; and the two studies that included subjects with strabismus showed an OR = 3.09, CI (95%) = [1.38, 7.00]. EDs were associated with an almost three times greater odds of having IS. We recommend the inclusion of vision testing in children with IS. The presence of eye diseases is associated with an almost three times greater odds of having scoliosis. The conditions that showed the greatest association were a severe decrease in visual acuity, followed by strabismus, and lastly refractive errors such as myopia and anisometropia.